Computer technology and classroom practices: continuity and change in school form - Villemonteix, François (Swiss Journal of Educational Research, 2018)
The research presented in this text focuses on common practices and speech teacher of primary school, computer technology users: Interactive Whiteboard (IWB), and Tablet. It comes against the often discourses about the radical transformation of teaching practices which may affect academic paradigm. We do not see a break with past practices found in the cases mentioned. It does not come out with earlier practices they would tend to reinforce, showing consistent with the classical school form and expectations connected to it. New complementarities appear between instruments, but they demand appropriate technical skills, uncommon among teachers of French primary school.